The Potential of Foxtail Millet as a Carbohydrate-Based Indonesian Local Functional Food - Andrea Natasha Candra; Bernadeth Caecilya Anggraini Halim; Franchel Kartasasmita; Gladys Gracia Christie; Jemima Patricia Pandyopranoto; Koo Felisha Andriani; Febrina Margaretha; Devita Mayanda Heerlie; Junaida Astina (Universitas Bio Scientia Internasional Indonesia, 2025)
Foxtail millet (Setaria italica L.) is a round-shaped cereal grain varied in colors and sizes and is part of the Poaceae family alongside sorghum and maize. It is one of the most extensively cultivated crops in Asia and Africa, as well as in several other developing countries. In 2014 alone, Asia and Africa produced 95% of the total global foxtail millet yield. Foxtail Millet itself is a good source of bioactive compounds such as minerals, phenolic compounds, amino acids, dietary fibers, carotenoids, sterols, unsaturated fatty acids, phytic acids, tocols, and anti-nutritive compounds. Due to these reasons, foxtail millet has several health benefits such as antioxidant activity, anti-hyperglycemic effects, anti-cholesterol effects, anti-hypertensive effects, and anthropometric effects. It has been mentioned that fox millet contains antioxidants, metal chelators, and reductants in the soluble and insoluble phenolic extracts which are beneficial as natural antioxidant sources. In animals, foxtail millet has also been proven to be safe and its benefit has been proven, specifically in terms of its gastroprotective effect. However, foxtail millet might cause an allergic reaction in humans due to cross-reactivity among different grains. Hence, the safety and efficacy of foxtail millet should be studied further. However, potentially, foxtail millet could be incorporated into a variety of aspects of the food industry. One of the functions is that it can be used to incorporate the flour in order to increase the nutritional properties, such as the mineral and fiber content of the flour itself.